Niveles de venta en la Ferretería “El Roble” de la ciudad de Babahoyo, periodo 2022. - Villavicencio Rizzo, Gertrudis María (2023)
In this case study was developed based on the research carried out in the hardware store "La Económica" of the city of Babahoyo, referring to the level of sales maintained by the aforementioned company. Using methods and techniques such as root cause, interview and survey to obtain information necessary to understand the factors involved in sales, it will be possible to find solutions for the company to take into account and improve the problems it has. In it I can see that the objective of studying the causes and problems of a company was met, taking into account that it will serve as a reference to apply in working life and avoid common mistakes in a company so that it can be successful.